Our health, our planet: a cross-sectional analysis on the association between health consciousness and pro-environmental behavior among health professionals. Issue 1 (2nd January 2020) - Shimoda, Akihiro; Hayashi, Hana; Sussman, David; Nansai, Keisuke; Fukuba, Isao; Kawachi, Ichiro; Kondo, Naoki
ABSTRACT: One possible predictive factor that affects both pro-environmental behavior and health behavior is health consciousness (a psychological state where an individual is aware of and involved in his/her health condition). We examined the relationship between health consciousness and two pro-environmental behaviors (recycling and green purchasing) within health professionals in a Japanese large hospital. Multivariate linear regression analysis revealed a significant association between health consciousness and recycling behavior, while there was no association between health consciousness and green purchasing behavior. We assume that health consciousness can certainly be a factor promoting pro-environmental behavior, but that it may have been insufficient to cause green purchasing, because of the organizational norm of recycling in the Japanese context. Given that there is previous evidence about the relationship between health consciousness and health behavior, health consciousness might be a predictive factor that encourages both health behavior and pro-environmental behavior simultaneously.